2010
DOI: 10.1136/ard.2010.140012
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of myelin autoreactive CD8+ T lymphocytes in patients with neuropsychiatric systemic lupus erythematosus

Abstract: These data strongly support the existence of a new immune effector mechanism responsible for CNS involvement in patients with NPSLE and suggest that analysing HLA-DR expression combined with myelin-specific tetramer staining on CD8+ T lymphocytes may be a valuable additional tool for the monitoring of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Patients were screened for their HLA-A2 status (clone BB7.2, Biolegend, San Diego, CA) as previously described (Contin-Bordes et al, 2011). To assess the frequency of melanocyte-antigen specific T cells, phycoerythrin-conjugated HLA-A0201 restricted pentamers loaded with MART-1(26-35) (ELAGIGILTV), tyrosinase (369-377) (YMDGTMSQV), or gp100 (154-162) (KTWGQYWQV) (ProImmune, Oxford, UK) were made by ProImmune using Pro5 MHC Class I pentamer technology.…”
Section: Detection Of Melanocyte-specific T Cellsmentioning
confidence: 99%
“…Patients were screened for their HLA-A2 status (clone BB7.2, Biolegend, San Diego, CA) as previously described (Contin-Bordes et al, 2011). To assess the frequency of melanocyte-antigen specific T cells, phycoerythrin-conjugated HLA-A0201 restricted pentamers loaded with MART-1(26-35) (ELAGIGILTV), tyrosinase (369-377) (YMDGTMSQV), or gp100 (154-162) (KTWGQYWQV) (ProImmune, Oxford, UK) were made by ProImmune using Pro5 MHC Class I pentamer technology.…”
Section: Detection Of Melanocyte-specific T Cellsmentioning
confidence: 99%
“…Effector CD8 + T cells are known to expand in the blood of SLE patients, and this expansion is related to the disease activity of SLE [39] . Contin-Bordes et al [40] demonstrated that IFNγ-secreting myelin-specific CD8 + T cells could be detected in the blood of NPSLE patients without antiphospholipid syndrome but with WM lesions, indirectly indicating that the WM lesions in these SLE patients were mainly demyelinating lesions. Previous studies have shown that CD8 + T cells play important roles in demyelinating diseases [41–43] .…”
Section: Discussionmentioning
confidence: 99%
“…Tetramer studies have provided insight into CD4 + T-cell molecular interactions, function, frequency, location, and response to therapy in other autoimmune diseases, including multiple sclerosis (32,33), type 1 diabetes (34, 35), rheumatoid arthritis (36), and celiac disease (37). Tetramers also have been used to detect IFNγ-secreting CD8 + T cells specific for myelin in neuropsychiatric SLE (38); however, the use of tetramers to identify and characterize self-reactive CD4 + T cells has not been reported in lupus. Here we describe MHC class II tetramers for use in studying CD4 + T cells in lupus-prone mice, and show that U1-70-specific CD4 + T cells produce IL-17A and express RORγt.…”
Section: Discussionmentioning
confidence: 99%